2021
DOI: 10.3390/ijms22052741
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Skeletal Muscle Growth and Organelle Biosynthesis: Practical Recommendations for Exercise Training

Abstract: The regulation of skeletal muscle mass and organelle homeostasis is dependent on the capacity of cells to produce proteins and to recycle cytosolic portions. In this investigation, the mechanisms involved in skeletal muscle mass regulation—especially those associated with proteosynthesis and with the production of new organelles—are presented. Thus, the critical roles of mammalian/mechanistic target of rapamycin complex 1 (mTORC1) pathway and its regulators are reviewed. In addition, the importance of ribosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 309 publications
(422 reference statements)
0
23
0
Order By: Relevance
“…Having established that WP can induce the same type of long-term adaptations that occur in human models of PRE, we next wanted to determine whether WP could induce some of the acute types of responses that are known to occur after a bout of PRE. For instance, in humans, it has been shown that PRE induces an acute: (i) increase in the phosphorylation state of various mitogen-activated protein kinases, (ii) activation of signaling by growth regulatory molecules, such as mTORC1, and (iii) increase in the rate of protein synthesis [ 21 , 42 , 43 ]. Thus, to determine whether WP could elicit these types of responses, mice were subjected to the control or WP conditions described in Figure 7 A.…”
Section: Resultsmentioning
confidence: 99%
“…Having established that WP can induce the same type of long-term adaptations that occur in human models of PRE, we next wanted to determine whether WP could induce some of the acute types of responses that are known to occur after a bout of PRE. For instance, in humans, it has been shown that PRE induces an acute: (i) increase in the phosphorylation state of various mitogen-activated protein kinases, (ii) activation of signaling by growth regulatory molecules, such as mTORC1, and (iii) increase in the rate of protein synthesis [ 21 , 42 , 43 ]. Thus, to determine whether WP could elicit these types of responses, mice were subjected to the control or WP conditions described in Figure 7 A.…”
Section: Resultsmentioning
confidence: 99%
“…Having established that WP can induce the same type of long-term adaptations that occur in human models of PRE, we next wanted to determine whether WP could induce some of the acute types of responses that are known to occur after a bout of PRE. For instance, in humans, it has been shown that PRE induces an acute: i) increase in the phosphorylation state of various mitogenactivated protein kinases, ii) activation of signaling by growth regulatory molecules such as mTORC1, and iii) increase in the rate of protein synthesis [21,41,42]. Thus, to determine whether WP could elicit these types of responses, mice were subjected to the control or WP conditions described in Figure 7A.…”
Section: Wp Induces An Increase the Rate Of Protein Synthesis And Alters The Phosphorylation State Of Proteins That Are Regulated By Pre mentioning
confidence: 99%
“…Physical exercise promotes the modulation of a large panel of cellular signaling pathways to promote metabolic and/or morphological changes that enhance performance (Bishop et al, 2019 ; Sanchez et al, 2019 ; Solsona et al, 2021 ). In recent years, repetition of short (≤30 s) all-out exercises were boosted in popularity because they can induce similar or higher gains of performance for a lower training volume compared to conventional endurance protocols (MacDougall et al, 1998 ; Barnett et al, 2004 ; Burgomaster et al, 2006 , 2008 ; Gibala et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%